There is a trend for the diagnosis of glaucoma to be made at an earlier stage in 2010 compared to 2008 in Oxford, United Kingdom. - Silva, D; Riaz, Y; Purbrick, R; Salmon, J (2013)
PURPOSE: New guidelines on glaucoma diagnosis and management were published by the National Institute of Clinical Excellence (NICE) in 2009. The aim of this study was to determine whether these guidelines on glaucoma referral have changed the numbers of patients diagnosed with glaucoma in Oxford and whether the severity of disease at presentation has altered between 2008 and 2010. METHODS: A retrospective study was undertaken of patients referred to a glaucoma case-finding clinic at the Oxford Eye Hospital in 2008 and 2010. Severity of glaucoma was assigned on the basis of the worse eye and defined according to mean deviation (MD) on 24-2 Humphrey visual field testing, with early glaucomatous visual field defects defined as MD less than -6 dB, moderate defects as MD between -6 and -12 dB and severe defects as MD more than -12 dB. Statistical analysis was undertaken using Chi squared and Mann Whitney tests. RESULTS: The number of referrals to this clinic increased from 521 patients in 2008, to 895 patients in 2010. 85 (16.3%) patients were diagnosed with ocular hypertension in 2008, compared to 144 (16.1%) in 2010. The number of patients diagnosed with glaucoma increased from 94 cases in 2008 to 113 cases in 2010, although the percentage of referrals diagnosed with glaucoma fell from 18.1% to 12.6%. More patients diagnosed with glaucoma in 2010 had early disease (61.9% in 2010 vs 48.8% in 2008, p = 0.03). Patients found to have glaucoma in 2010 had less severe visual field defects than in 2008: patients presented with a lower mean deviation (-6.36 dB in 2010, -7.95 dB in 2008, p = 0.03) and lower pattern standard deviation (5.44 dB in 2010, 6.64 dB in 2008, p = 0.02). However, there was no significant difference between age of presentation (65.1 years in 2010, 65.2 years in 2008, p = 0.82), and IOP (21.62 mmHg in 2010, 23.15 mmHg in 2008, p = 0.22). CONCLUSIONS: There has been a significant increase in number of referrals to the glaucoma case-finding clinic in Oxford between 2008 and 2010. The introduction of NICE referral guidelines in 2009 has had the benefit of increasing the absolute number of patients detected with glaucoma and has resulted in more patients being diagnosed with early disease. More effort needs to be made to reduce the number of false positive referrals. In addition, the guidelines on referral of individuals with ocular hypertension need to be reconsidered.